Estimation of potential fresh water reserves in icebergs - M. S. Krass (Лëд и снег, 2017)
According to the forecast of the global shortage of fresh water it is expected that the global demand for drink‑ ing water will be increased up to 400 km3 per a year. As the main potential resources of drinking water it is proposed to use table Antarctic icebergs. Mathematical and phenomenological models of heat exchange between the icebergs and the environment, and a process of melting of ices floes in the warm sea water are discussed. The ablation processes on the daily and lower surfaces of icebergs at different modes of towing them to points of utilization is analyzed. The most optimal technology is to fill tankers with water taken from the freshwater layer under icebergs, and then subsequent delivery of the water to points of utilization. Using of the phenomenon of fresh-salt stratified Lake Vanda is considered as one of promising technologies of the industrial water production.